A Descriptive Study on the Population of Patients with Inflammatory Bowel Disease at the Veterans Affairs Caribbean Healthcare System in San Juan - Toro, Doris H.; Class-Vázquez, Walisbeth; Rosa-Cortés, Pedro A.; Rodríguez-Berrios, Frances (Puerto Rico Health Sciences Journal, 2020)
Objective: Inflammatory bowel disease (IBD) comprises a group of related conditions characterized by idiopathic inflammation of the gastrointestinal (GI) tract. Several studies have described the epidemiology of IBD in Puerto Rico (PR) but none have included the US military and Veteran population. The goal of this study was to describe the prevalence of IBD in this population as well as to describe patients’ characteristics. Methods: We conducted a retrospective analysis of 163 patients using data gathered from electronic medical records of Veterans who received care at the VA Caribbean Healthcare System (VACHS) and the diagnosis of IBD between October 1, 2010 and September 30, 2015. The prevalence out of 100,000 in our study was calculated for each Fiscal Year. Results: Overall, the prevalence of IBD markedly increased among VA patients. Among 163 patients who met inclusion criteria, 7 (4.3%) patients had a diagnosis of undetermined IBD, 45 (27.6%) had Crohn’s disease (CD) and 111 (68.0%) had ulcerative colitis (UC). This information was used to compare the epidemiologic data of IBD in the population receiving care at the VACHS with the epidemiologic data of IBD in the general population in PR. Conclusion: This is the first study to describe the prevalence of IBD and to describe additional characteristics of patients with IBD receiving care at the VACHS.